Propriedades da madeira de eucalipto para a produção de madeira serrada - França, Frederico José Nistal (2014)
The present work aimed to describe the characteristics of trees and wood properties of clones of the 13-year-old Eucalyptus grandis x Eucalyptus urophylla hybrid, seeking for selection of genetic material for production of lumber. Crown size , diameter at breast height (DBH) and longitudinal growth strain (LGS) in the North and South position of the stems of 20 different clones of the hybrid trees were evaluated. There were significant differences between clones by Scott-Knott test (p = 0.05) in the three parameters. LGS variation occurred between the North and South directions, more pronounced in the northern position. The LGS showed no significant correlation (p=0.3885) with the DBH. Seven clones were selected showing better characteristics (DBH and reduced LGS). The rate of logs end splits and cracks in green and air dried boards was analyzed. Interlocked grain was evaluated by maximum angle deviation (MAD) and interlocked grain index (IGI) methods. Physical properties (specific gravity and shrinkage) and mechanical properties (compression parallel to grain, static bending and Janka hardness) were analyzed. The results showed that end Split of logs and cracks on boards showed low correlation with LGS. There was a high correlation between the interlocked grain index with splits and cracks, leading to realize that the interlocked grain reduces those type of defects.